6=3-k

Simple and best practice solution for 6=3-k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=3-k equation:


Simplifying
6 = 3 + -1k

Solving
6 = 3 + -1k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add 'k' to each side of the equation.
6 + k = 3 + -1k + k

Combine like terms: -1k + k = 0
6 + k = 3 + 0
6 + k = 3

Add '-6' to each side of the equation.
6 + -6 + k = 3 + -6

Combine like terms: 6 + -6 = 0
0 + k = 3 + -6
k = 3 + -6

Combine like terms: 3 + -6 = -3
k = -3

Simplifying
k = -3

See similar equations:

| 6x+9(x-3)=5(x-8) | | 82-b= | | 3m-m-m-m+2m=16 | | 4(x+9)=-3(2x-9)+4x | | 22x-10=0 | | 15=19+2(q-18) | | 9x-3(x-2)=2(x-3)+9 | | -6y=-20 | | -3x^2-30x^2-72x=0 | | -6y=-29 | | -s+6s+16s-20s=11 | | 9(x-9)+5x=9-5(x-8) | | 2(x+5)=3(4+x) | | 6y-7(y-3)=8-7(y-3) | | x+(x*.0825)=65.35 | | 6.3a+4.5/2=10.2 | | 5t+2t+2t-3t-3t-2=13 | | 59-e=58 | | 4(d-2.13)-2.66=3(d-2.27) | | -(5x-11)+4(3x+8)= | | -8x+10=-6x+20 | | 31x-8(3x-0.745)=6x+0.205 | | 2(x+5)+3(4+x)= | | 4x+5y-y+3= | | 2c+7=-5c+2 | | x^4-14x-120=0 | | 12y-9y-8y+7y=12 | | -9+y=-12 | | 7(p-5)=21 | | -6+8x=6+9x | | 2(4x+1)=3x+17 | | 5(z-5)+8z-4= |

Equations solver categories